Multipurpose watermarking based on hybrid strategies - Sivananthamaitrey, P; Rajesh Kumar, P (International Journal of Engineering and Technology, 2018)
Dual digital watermarking has emerged as a successful solution for copyright protection, tamper detection and localization. However, several problems related to the robustness, capacity, tampered area detection still mystifying. This paper presents a high capacity dual watermarking mechanism for digital colour images. An invisible robust watermark is embedded in the Green component of the host image by using a hybrid combination of Stationary Wavelet Transform (SWT) and Singular Value Decomposition (SVD) for copyright protection. A fragile invisible watermark based on the Least Significant Bit (LSB) replacement approach is embedded in the Blue composition of the image for tamper detection and localization. The proposed technique focuses on robustness and imperceptibility while maximizing embedding capacity that makes this technique a multipurpose watermarking scheme.